Pendekatan Scientific Berbantuan Media Pembelajaran Puzzle dalam Meningkatkan Curiosity dan Kemampuan Analogi Mahasiswa pada Pembelajaran Ekonomi - Nur, Andi St. Aisyah; Ramli, Anwar; Inanna, Inanna (JEKPEND: Jurnal Ekonomi dan Pendidikan, 2021)
This research is based on real conditions in the field, namely the low curiosity and analogy ability of students at the University of Muhammadiyah Bone, Campus 3 Kahu, through economics learning, especially in the subject of Introduction to Economics II, Taxation on the Basics of Social Sciences which has not used a scientifically assisted approach. puzzle learning media in the learning process. This type of research uses quantitative research with the type of research design, namely Quasi Experimental Design with the type of "Nonequivalent Control Group Design". Based on the results of the recapitulation of student scores in the experimental class, the average score was 76.92 and the control class was 57.41, which means that the value of the experimental class (with a scientific approach assisted by puzzle learning media) is higher than the control class (direct approach). Meanwhile, based on the SPSS output from the Independent Samples Test obtained by the researcher, it can be concluded that the statistical test in the t-test above uses two-tailed testing which can be concluded that the value of Sig. of 0.000 < 0.05 based on the decision rule of the t-test, H1 is accepted and H0 is rejected. Thus, it can be concluded that there is an Influence of Scientific Approach on Curiosity and Analytical Ability of Students in Economic Learning at Muhammadiyah University Bone, Campus 3 Kahu, Bone Regency in economic learning